Determination of the minimal important difference for Dyspnoea‐12 questionnaire in patients with COPD, after pulmonary rehabilitation. (18th December 2020) - Beaumont, Marc; Le Garrec, Mélanie; Péran, Loic; Berriet, Anne‐Cécile; Le Ber, Catherine; Pichon, Romain; Cabillic, Michel
Abstract: Introduction: The authors of the international task force about the management of Dyspnoea recommend assessing sensory and affective components of dyspnoea. The Dyspnoea‐12 questionnaire (D‐12) allows to assess both components of dyspnoea. D‐12 is valid and reliable but its sensitivity to pulmonary rehabilitation was not studied. The aim of this study was to estimate the minimal important difference (MID) for D‐12 in COPD patients undergoing a pulmonary rehabilitation programme (PRP). Methods: Severe or very severe COPD patients undergoing a PRP were included. Dyspnoea was assessed using D‐12, MMRC dyspnoea scale, London chest of Activity of Daily Living questionnaire (LCADL). Quality of life was assessed using Saint‐George respiratory questionnaire (SGRQ) and COPD assessment Test (CAT); exercise capacity using 6‐Minute walk Test (6MWT) and 1‐minute sit to‐stand test (1STST). The MID was evaluated using distribution and anchor‐based methods. Results: Sixty patients (age: 64.4 ± 8.2; FEV1 (%): 28.6 ± 8.1) were included. At the end of the PRP, patients had significantly decreased their dyspnoea measured with D‐12, MMRC, LCADL (D‐12:23.9 ± 8.9 to 17.6 ± 9.4; MMRC: 3 ± 0.7 to 2.2 ± 1.1, LCADL: 38 ± 13.9 to 31.6 ± 11; p < 0.0001). Using the distribution‐based analysis, MID of −2.67 (standard error of measurement) or −4.45 (standard deviation) was found. According to methodology, we could only use SGRQ as anchor. With SGRQ as anchor, the receiver operating characteristic curve identified MID for the change in D‐12 at −6.1 (sensibility: 58%, specificity: 79%). The correlation with SGRQ was modest ( r = 0.33), so the calculated MID should be interpreted with caution. Conclusion: D‐12 is a good tool to assess the decrease of dyspnoea after PR. We propose MID of −6 points. However, Future estimates of MID for the D‐12 should use anchors that are more strongly correlated with it.